PaleoMaps: GIS based Palaeoenvironmental data collection for the Last Interglacial (125ka) of Egypt - Henselowsky, Felix; Bubenzer, Olaf (CRC806-Database, 2017)
The growing number of paleoenvironmental data, GIS-based analyses and modelling allows us to produce PaleoMaps for a given area. However, the „translation“ of paleoenvironmental information in maps is even more complex, than producing maps as an illustration of the present. The CRC 806 “Our Way to Europe” provides the background to study the culture-environment interaction and human mobility in the Late Quaternary. Northeastern Africa during the Last Interglacial is thereby an important region and timespan. From this point, a first conceptual design for a PaleoMap of Egypt for the time about 125 ka ago is presented.
Gesehen am 06.07.2017